2018
DOI: 10.1021/acs.joc.7b03174
|View full text |Cite
|
Sign up to set email alerts
|

Transfer Hydrogenation of Aldehydes and Ketones with Isopropanol under Neutral Conditions Catalyzed by a Metal–Ligand Bifunctional Catalyst [Cp*Ir(2,2′-bpyO)(H2O)]

Abstract: A Cp*Ir complex bearing a functional bipyridonate ligand [Cp*Ir(2,2'-bpyO)(HO)] was found to be a highly efficient and general catalyst for transfer hydrogenation of aldehydes and chemoselective transfer hydrogenation of unsaturated aldehydes with isopropanol under neutral conditions. It was noteworthy that many readily reducible or labile functional groups such as nitro, cyano, ester, and halide did not undergo any change under the reaction conditions. Furthermore, this catalytic system exhibited high activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(38 citation statements)
references
References 65 publications
0
33
0
Order By: Relevance
“…The alkene C=C double bond remained unreacted under these conditions (entry 16), and in the case of diketone 7 l, the corresponding dialcohol 8 l was obtained as a major product (entry 12). Aliphatic ketones ( Table 2, entries [14][15][16][17][18] were also effectively hydrogenated to give the corresponding alcohol products in good yields.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The alkene C=C double bond remained unreacted under these conditions (entry 16), and in the case of diketone 7 l, the corresponding dialcohol 8 l was obtained as a major product (entry 12). Aliphatic ketones ( Table 2, entries [14][15][16][17][18] were also effectively hydrogenated to give the corresponding alcohol products in good yields.…”
Section: Resultsmentioning
confidence: 99%
“…Bioinspired Ir complexes with dihydroxy‐substituted bipyridine and bipyrimidine were also developed that act as efficient catalysts for reversible hydrogenation of CO 2 and dehydrogenation of formic acid . Recently, Li and co‐workers showed that Ir complex with 6,6′‐dihydroxy‐2,2′‐bipyridine is an active catalyst of TH of aldehydes and ketones, while unsubstituted and mono‐hydroxy‐substituted bipyridine analogs show no activity or much lower product yields …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…isopropanol, 82 C, N 2 , 6 hr 93 465 [43] 6 (1.0) HCOONa/HCO 2 H, H 2 O, pH = 2.5, 80 C, 12 hr 96 96 [44] 7 (0.5) glucose, H 2 O, Na 2 CO 3 , 100 C, 20 h 86 172 [45] 8 Au-SiO 2 (1.0) 2,4,6-trimethylpyridine, iPrOH, H 2 (6 bar), 100 C, 24 hr 100 100 [46] 9 Ni-nanoparticles (10.0) HCOONH 4 , THF, 25 C, N 2 , 1.5 hr 85 8.5 [47] 10 Pd-nanoparticles (1.0) H 2 , H 2 O, rt, 6 hr 90 90 [48] stirred for 12 hr at 80 C. Then the reaction mixture was filtered and the filtrate was concentrated under vacuum to yield the crude product. The crude product was purified by column chromatography, eluting with hexane/EtOAc, to afford the desired product.…”
Section: General Procedures For the Reduction Of Aldehydes To Alcohomentioning
confidence: 99%
“…The most well-known of these would be the Meerwein-Ponndorf-Verley (MPV)-type reduction using 2-propanol as a hydrogen donor. Although an aluminum catalyst is typically used in MPV-type reductions [5,6], many highly efficient systems using transition metal catalysts have been reported [7][8][9][10][11][12]. However, MPV-type reduction depends on the equilibrium between alcohols and carbonyl compounds; therefore, a large excess of 2-propanol as a hydrogen donor must be used to obtain an alcohol in high yield.…”
Section: Introductionmentioning
confidence: 99%